2015
DOI: 10.4238/2015.june.29.18
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Pro12Ala and His447His polymorphisms and susceptibility to Alzheimer’s disease: a meta-analysis

Abstract: ABSTRACT. We investigated whether Pro12Ala (C→G) and His447His (C→T) polymorphisms of the peroxisome proliferatoractivated receptor gamma (PPARg) gene are associated with susceptibility to Alzheimer's disease (AD). We conducted a metaanalysis of the associations between the PPARg Pro12Ala and His447His polymorphisms and AD in subjects. The meta-analysis was performed according to the apolipoprotein E (APOE) ɛ4 allele status. A total of eight studies were considered in our meta-analysis, comprising 2948 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similarly, in the second study case, we found that the differentially expressed (such as VDR [ 60 ], SP1 [ 61 ], CREB1 [ 62 ], and RELB [ 63 ]) and the non-differentially expressed (such as ESR1 [ 64 ], PPARG [ 65 ], ESR2 [ 66 ], and PPARD [ 67 ]) genes are AD-related genes. Besides this, we also found that some of the hub nodes in the network are not included in the AD-related gene dataset, such as the differentially expressed genes RXRA , STAT3 , STAT1 , PSMD14 , and so forth, and the non-differentially expressed HNF4A , PGR , ESRRA , THRB , and so forth, which are worth paying more attention to in further study.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, in the second study case, we found that the differentially expressed (such as VDR [ 60 ], SP1 [ 61 ], CREB1 [ 62 ], and RELB [ 63 ]) and the non-differentially expressed (such as ESR1 [ 64 ], PPARG [ 65 ], ESR2 [ 66 ], and PPARD [ 67 ]) genes are AD-related genes. Besides this, we also found that some of the hub nodes in the network are not included in the AD-related gene dataset, such as the differentially expressed genes RXRA , STAT3 , STAT1 , PSMD14 , and so forth, and the non-differentially expressed HNF4A , PGR , ESRRA , THRB , and so forth, which are worth paying more attention to in further study.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, emerging evidence suggests that PPARγ effectively regulates microglia activation under physiological and pathological conditions, facilitating Aβ microglial phagocytosis [53]. In addition, PPARγ polymorphisms have been studied in AD; however, the results are controversial and inconclusive [54].…”
Section: Peroxisome Proliferator-activated γ Receptormentioning
confidence: 99%